Analisis Kesulitan Siswa Menerjemahkan Soal Cerita Ke dalam Model Matematika pada Materi Aljabar (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to describe students' difficulties in translating word problems into mathematical models in algebra material. Using a qualitative approach, the subjects were seventh-grade students at SMP Negeri 2 Tasikmalaya in the 2024/2025 academic year. Data were collected through questionnaires, interviews, and documentation. The results show that students struggled to understand the meaning of word problems and convert them into correct equations. Common errors included misconceptions about algebraic symbols, such as treating variables as fixed numbers and misusing the equal sign. In addition, students had difficulty identifying essential information needed to construct a mathematical model. Learning activities that focused only on procedural calculations further contributed to these challenges. This study recommends the use of more contextual and meaningful learning approaches, such as Problem-Based Learning and Realistic Mathematics Education, to help students better understand the relationships within problems and accurately express them through appropriate mathematical representations.. Penelitian ini bertujuan untuk mendeskripsikan kesulitan siswa dalam menerjemahkan soal cerita ke dalam model matematika pada materi aljabar. Dengan pendekatan kualitatif, subjek penelitian adalah siswa kelas VII SMP Negeri 2 Tasikmalaya tahun ajaran 2024/2025. Data dikumpulkan melalui angket, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa siswa mengalami kesulitan dalam memahami makna soal cerita dan menyusunnya menjadi persamaan yang tepat. Kesalahan yang muncul meliputi pemahaman yang keliru terhadap simbol aljabar, seperti menganggap variabel sebagai angka tetap dan tidak tepat menggunakan tanda sama dengan. Selain itu, siswa juga tampak kesulitan menentukan informasi penting yang diperlukan untuk membangun model matematika. Pembelajaran yang hanya berfokus pada prosedur perhitungan turut memperkuat kesulitan ini. Penelitian ini merekomendasikan penggunaan pendekatan pembelajaran yang lebih kontekstual dan bermakna, seperti Problem-Based Learning dan Realistic Mathematics Education, agar siswa dapat lebih memahami hubungan antar informasi dalam soal dan menyusunnya dalam bentuk model yang benar.